The fall of the Berlin Wall, the collapse of the USSR and the end of Cold War. A chain of surprises 'Too Big' to be predicted - Marsili, M. (Political Reflection Magazine, 2021)
The fall of the Berlin Wall, on the night of 9 November 1989, marked the beginning of the collapse of the Soviet Union and the end of the Cold War. Distinguished scholars of the realist school have developed different theories on the root causes and predictability of the end of the Cold War and have sought to find whether the end of the conflict between the Western and the Eastern bloc was predictable, and under which terms it could be settled.